Preliminary Results on Deformations of the Central North Anatolian Fault Zone - Kayhan Aladoğan; Mehmet Nurullah Alkan; İbrahim Tiryakioğlu; Hasan Hakan Yavaşoğlu; Halil İbrahim Solak; Cemil Gezgin; Ali Özkan; Eda Esma Eyübagil; Furkan Şahiner; Ece Bengünaz Çakanşimşek; Zafer Köse (Hittite Journal of Science and Engineering)

(untitled)
The North Anatolian Fault Zone (NAFZ) in the north of Türkiye is considered one of the most active faults on earth and have caused many major earthquakes in the last century. Surface ruptures by those earthquakes indicate that this tectonic feature consists of many segments, which reveal different characteristics in terms of geometry and mechanism. NAFZ lies along between Bingöl in the eastern Turkey and Saros Gulf in the west. This study focuses on the central part of the NAFZ between Niksar and Ilgaz provinces. In addition to the main branch, the central section of the NAFZ also contains two sub-branches extending southward: Merzifon-Esençay and Sungurlu Faults. In the literature, there are several studies for the region, however a comprehensive study mainly focusing on the main branch of the NAFZ and its sub-branches along the central NAFZ has not been conducted yet, which would fully reveal the fault mechanism and seismic potential in the region. The aim of this study is to derive an up-to-date high-spa-tial-resolution Global Navigation Satellite Systems (GNSS) velocity field for the central NAFZ and to correlate with the strain accumulations along the faults. Based on this, a high-spatial-resolution GNSS network consisting of 60 sites was established enclosing the central NAFZ. The previously archived GNSS data for the same observation sites were collected from the different studies in the region and a new GNSS campaign measurement was conducted between October 2023 and February 2024. All GNSS data were processed using GAMIT/GLOBK software, and the results indicate the GNSS velocities ranging from 3-30 mm/year and their associated uncertainties of maximum ± 1.5 mm/year with respect to the Eurasian tectonic plate.